Anatomical patterns of cleft lip and palate deformities among neonates in Mekelle, Tigray, Ethiopia; implication of environmental impact - Konjit K. Bekele; Peter E. Ekanem; Berhanu Meberate (BMC, 2019)
Abstract Background Cleft lip and palate deformities are considered one of the most common birth defects of the head and neck that pose significant medical, psychosocial and financial burdens on the affected individuals and families, especially in low income communities. The etiology and pathogenesis of cleft lip and palate is complex and is known to involve genetic and/or environmental factors. Objective To assess the patterns of anatomical cleft lip and palate deformities among neonates in Mekelle and Ayder Comprehensive Specialized hospitals, Tigray, Northern Ethiopia. Methods A hospital-based retrospective study was conducted from May 2017 to June 2017 at Mekelle and Ayder Comprehensive Specialized hospitals, both in Mekelle city. Data was collected from all medical charts of neonates registered from 2011 to 2016 and analyzed using SPSS version 21.0 and OpenEpi software. Results were presented using tables and graphs; Chi-square test was used to look for an association between variables, odds ratio to determine the strength of association of selected variables using multinomial logistic regression model, while Fisher Exact (Clopper-Pearson) was used to compare yearly prevalence. Results Of 37,152 neonatal charts analyzed, 119 (0.32%) cases were identified as having cleft deformities. 38.7, 17.6, and 43.7% of this figure had cleft lips, cleft palates and both cleft lip and palate respectively. 46 (38.7%) neonates had lateral patterns of cleft lip deformities with 56.5% located unilaterally on the right and 43.5% unilaterally on the left. Of 52 (43.7%) neonates with cleft lip and palate deformities, 40.4% were located bilaterally while 38.5 and 21.2% were located unilaterally on the left and right, respectively. Associated malformations were: cardiac (3.4%), central nervous system (1.7%) and limb deformities (5.9%). The overall prevalence of cleft deformities was found to be 3.11 per 1000 live births. Conclusion The study showed a higher prevalence of cleft deformities than that reported in Addis Ababa and some other African countries. A higher occurrence of left unilateral pattern of cleft lip and palate was observed whereas a higher right unilateral pattern of cleft lip was identified. The higher prevalence of cleft lip and palate recorded in this region of Ethiopia may reflect an environmental impact.